Piezoelectric smart biomaterials for bone and cartilage tissue engineering - Jaicy Jacob (Inflammation and Regeneration, 2018)
Abstract Tissues like bone and cartilage are remodeled dynamically for their functional requirements by signaling pathways. The signals are controlled by the cells and extracellular matrix and transmitted through an electrical and chemical synapse. Scaffold-based tissue engineering therapies largely disturb the natural signaling pathways, due to their rigidity towards signal conduction, despite their therapeutic advantages. Thus, there is a high need of smart biomaterials, which can conveniently generate and transfer the bioelectric signals analogous to native tissues for appropriate physiological functions. Piezoelectric materials can generate electrical signals in response to the applied stress. Furthermore, they can stimulate the signaling pathways and thereby enhance the tissue regeneration at the impaired site. The piezoelectric scaffolds can act as sensitive mechanoelectrical transduction systems. Hence, it is applicable to the regions, where mechanical loads are predominant. The present review is mainly concentrated on the mechanism related to the electrical stimulation in a biological system and the different piezoelectric materials suitable for bone and cartilage tissue engineering.